1956
DOI: 10.1111/j.1365-2621.1956.tb16915.x
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Comparison of the Two‐sample and Triangular Binomial Designs

Abstract: The relative sensitivities of the two-sample and triangular designs, in cases where quality may be stated unambiguously, have been much discussed. From a classical standpoint, using a binomial mathematical model, the triangular technique should be more efficient than the two-sample (9). This arises from the differences in the chance probability for each design.The two-sample comparison consists in the presentation of two samples (different in intensity of quality) to the taster, who is required to denote one a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…For the triangle test, these include testing procedures such as the binomial test (e.g., Lockhart, 1951) and estimation of a dose-response relation using a model (Bock & Jones, 1968;Filipello, 1956) that was recently named the triangular constant method model (Frijters, 1979).…”
mentioning
confidence: 99%
“…For the triangle test, these include testing procedures such as the binomial test (e.g., Lockhart, 1951) and estimation of a dose-response relation using a model (Bock & Jones, 1968;Filipello, 1956) that was recently named the triangular constant method model (Frijters, 1979).…”
mentioning
confidence: 99%
“…This was shown for a variety of stimuli (Dessirier, Seiffermann, & O'Mahony, 1999;Filipello, 1956;Frijters, Blauw, & Vermaat, 1982;Masuoka et al, 1995;O'Mahony & Goldstein, 1987;O'Mahony & Odbert, 1985;Stillman, 1993;Tedja et al, 1994;Wasserman & Talley, 1969). The two distribution, equal variance model, as described above, cannot account for this satisfactorily.…”
Section: A Challengementioning
confidence: 86%
“…However, in the triangle test, they were asked first to determine difference and then intensity of the samples. Filipello (1956) also showed that the triangle design was not as sensitive as the paired-comparison, but this was in the testing of thresholds of simple taste solutions and not complex food systems. Gridgeman (1970) showed that pairedcomparison results more sharply distinguished preferential differences between two treatments, but compared this to a more psychologically complex two-stage triangle test.…”
Section: Introductionmentioning
confidence: 93%